2023
DOI: 10.1158/1078-0432.ccr-22-3156
|View full text |Cite
|
Sign up to set email alerts
|

Functional Homologous Recombination Assay on FFPE Specimens of Advanced High-Grade Serous Ovarian Cancer Predicts Clinical Outcomes

Abstract: Purpose: Deficiency in homologous recombination (HR) repair of DNA damage is characteristic of many high-grade serous ovarian cancers (HGSC). It is imperative to identify patients with homologous recombination deficient (HRD) tumors as they are most likely to benefit from platinum-based chemotherapy and PARP inhibitors (PARPi). Existing methods measure historical, not necessarily current HRD, and/or require high tumor cell content which is not achievable for many patients. We set out to develop a clinically fe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…However, somatic alterations analysis of the #C218 resistant tumor through WES revealed a deletion spanning from intron 6 to 7 to the middle of exon 10 on chromosome 17 (chr17:g.43092980-43102933del) both in tumor and iPDCs, causing a potential in frame transcript and restoration of BRCA1 activity. In addition, functional HRD test ( 32 ) based on RAD51 foci on the formalin fixed tissue samples of these three tumors showed that the olaparib resistant #C218 sample was HRP while other two samples were found to be HRD, supporting the notion of HR restoration in #C218. Together, the results from scRNA-seq and WES showing enrichment of pathways related to cell cycle, proliferation, and drug resistance, combined with restoration of HR proficiency suggest possible mechanisms of therapy resistance leading to progressive disease in olaparib resistant patient #C218.…”
Section: Resultsmentioning
confidence: 63%
“…However, somatic alterations analysis of the #C218 resistant tumor through WES revealed a deletion spanning from intron 6 to 7 to the middle of exon 10 on chromosome 17 (chr17:g.43092980-43102933del) both in tumor and iPDCs, causing a potential in frame transcript and restoration of BRCA1 activity. In addition, functional HRD test ( 32 ) based on RAD51 foci on the formalin fixed tissue samples of these three tumors showed that the olaparib resistant #C218 sample was HRP while other two samples were found to be HRD, supporting the notion of HR restoration in #C218. Together, the results from scRNA-seq and WES showing enrichment of pathways related to cell cycle, proliferation, and drug resistance, combined with restoration of HR proficiency suggest possible mechanisms of therapy resistance leading to progressive disease in olaparib resistant patient #C218.…”
Section: Resultsmentioning
confidence: 63%
“…In addition to newly produced scRNA-seq data from 25 tumors, the scRNA-seq cohort contains data from three clinical specimens originally published in 33 , 21 specimens originally published in 16 , and two specimens originally published in 67 . Genomic HRD annotations were previously published in 24,68,69 , and bulk RNAseq in 70 . The DECIDER study was approved by the Ethics Committee of the Hospital District of Southwest Finland (ETMK 145/1801/2015).…”
Section: Methodsmentioning
confidence: 99%
“…This can be performed on treatment-naive as well as post-chemotherapy specimens with low tumour content, thereby providing dynamic HRD monitoring. Although the assay predicted response to platinum therapy, it lacks prospective validation and predictive value for PARPi therapy [ 28 ].…”
Section: Dna Damage Repair (Ddr) Pathwaysmentioning
confidence: 99%